The world bank and the rhetoric of social accountability in Ethiopia - Harrison Brennan, K; Kate Harrison Brennan (2014)
Following the controversial Federal election in Ethiopia in 2005, in which the ruling party regained power amidst allegations of state-sanctioned violence, the World Bank, along with other bilateral donors, stopped providing Direct Budget Support. In 2006, the Bank formed an agreement with the Ethiopian Government for an International Development Association (IDA) grant for the Protection of Basic Services. The project design for the grant was one of the most complex in the Bank's operations worldwide and featured a component for the implementation of social accountability, financed by a Multi-donor Trust Fund. This thesis critically examines the evolution within the Bank of this policy of 'social accountability' in relation to aid. Situated within the literature on the re-politicisation of aid, it questions the plausibility of implementing such a policy in Ethiopia where the dominant party was seeking ways to extend its power over society. Fieldwork for this thesis was conducted at the World Bank in Washington D.C. and in Ethiopia: in Addis Ababa, and in the region of Tigray. The evidence assembled in this thesis is drawn from 135 semi-structured interviews and a range of primary source documents. Using an historical method, this thesis argues that the primary purpose of social accountability was rhetorical and the deployment of this language by actors was cynical. Not only did donors have a limited purchase on a complex social reality in Ethiopia, but they also tolerated the misuse of social accountability by the dominant party to extend the power of the state. What was produced in Ethiopia was radically outside of what donors imagined, although they were remarkably relaxed about this fact. This thesis challenges the conventional assumptions that actors in aid negotiations are rational and that aid programs involve the imposition of rationalising high-modernist schemes.